Tissue biomimicry using cross-linked electrospun nonwoven fibre composites - Illner Sabine; Arbeiter Daniela; Teske Michael; Khaimov Valeria; Oschatz Stefan; Senz Volkmar; Grabow Niels; Kohse Stefanie; Schmitz Klaus-Peter (Current Directions in Biomedical Engineering, 2019)
Mimicking the structural properties of natural tissue was aimed to be achieved by combining complementary mechanical properties of materials showing high tensile strength with those of high elasticity. By using two polymers with different properties, the advantages of both can be combined to access innovative materials for biomedical applications. Dual co-electrospinning was established to generate biocompatible nonwoven fibre composites with fused properties from polyamide (PA6) and polyurethane based silicone elastomers (PU-co-Si), respectively. By electrospinning both compounds simultaneously, significant advantages, such as combining different fibre thicknesses and mechanical properties, are accessible. Furthermore, the effect on the fibres via an optional post-processing step in the shape of different thermal treatments was investigated. Initial results concerning surface morphology, biocompatibility and tensile properties of the obtained electrospun nonwovens are very auspicious. Thus, the suitability of two complementary polymer classes for tissue biomimicry through a synthetic approach was shown, offering the opportunity of novel implant materials for permanent replacement of biological tissue.